Agriculture organizations against monsanto in Argentina: The effects on state regulations - Borja Jaramillo, Juan Carlos (2019)
Since the beginning of the XXI century, particular phenomena have risen regarding traditional configurations of power with States, revealing that these may not be its main source. This has been increasingly noticed by academics as new actors, such as multinational companies and civil society organizations, take more importance in topics that had been assigned exclusively to the State. In fact, the latter has been less perceived as the sole actor to participate in processes that can affect everyone, such as the development of regulations. To study the interactions between the State, multinational companies and civil society, this dissertation will study the case of the attempts of Monsanto to influence the Argentinian State on implementing systems that benefit the company in local regulations, specifically the Law of Seeds and Phytogenetic Creations, and the resistance of local society to prevent this to be accomplished between 1990 and 2017. This will be analyzed, through the Critical Theory of Robert Cox, a relevant framework to study the interactions between the actors from a diachronic scope, for which the method of historical analysis will be used.